Depressive symptoms in urban population samples in Russia, Poland and the Czech Republic - Bobak, Martin; Pikhart, Hynek; Pajak, Andrzej; Kubinova, Ruzena; Malyutina, Sofia; Sebakova, Helen; Topor-Madry, Roman; Nikitin, Yuri; Marmot, Michael (The British journal of psychiatry, 2006)
BACKGROUND: Relatively little is known about depression in countries that were formerly part of the Soviet Union, especially Russia. AIMS: To investigate the rates and distribution of depressive symptoms in urban population samples in Russia, Poland and the Czech Republic. METHOD: A cross-sectional study was conducted in randomly selected men and women aged 45-64 years (n=2151 in total, response rate 69%) in Novosibirsk (Russia), Krakow (Poland) and Karvina (Czech Republic). The point prevalence of depressive symptoms in the past week was defined as a score of at least 16 on the Center for Epidemiological Studies Depression scale. RESULTS: In men the prevalence of depressive symptoms was 23% in Russia, 21% in Poland and 19% in the Czech Republic; in women the rates were 44%, 40% and 34% respectively. Depressive symptoms were positively associated with material deprivation, being unmarried and binge drinking. The association between education and depression was inverse in Poland and the Czech Republic but positive in Russia. CONCLUSIONS: The prevalence of depressive symptoms in these eastern European urban populations was relatively high; as in other countries, it was associated with alcohol and several sociodemographic factors.
Keywords: Urban Health; Humans; lidé středního věku; socioekonomické faktory; prevalence; Alcohol Drinking; pití alkoholu; Female; rizikové faktory; Polsko; lidé; Poland; Socioeconomic Factors; ženské pohlaví; Depressive Disorder; zdraví ve městech; Male; depresivní poruchy; Middle Aged; Czech Republic; Rusko; Cross-Sectional Studies; Russia; Prevalence; Česká republika; mužské pohlaví; průřezové studie; Risk Factors